The Society for Worldwide Interbank Financial Telecommunication (SWIFT) Cooperative governance for network innovation, standards, and community - Scott, Susan V. (Routledge Global Institutions Series, 2014)
This book traces the history and development of a mutual organization in the financial sector called SWIFT, the Society for Worldwide Interbank Financial Telecommunication. Over the last 40 years, SWIFT has served the financial services sector as proprietary communications platform, provider of products and services, standards developer, and conference organizer (Sibos). Founded to create efficiencies by replacing telegram and telex (or "wires") for international payments, SWIFT now forms a core part of the financial services infrastructure. It is widely regarded as the most secure trusted third-party network in the world serving 212 countries and over 10,000 banking organizations, securities institutions, and corporate customers. Through every phase of its development, SWIFT has maintained the status of industry cooperative, thus presenting an opportunity to study broader themes of globalization and governance in the financial services sector. In this book the authors focus on how the design and current state of SWIFT were influenced by its historical origins, presenting a comprehensive account in a succinct form which provides an informative guide to the history, structure, activities, and future challenges of this key international organization. This work will be of great interest to students and scholars in a wide range of fields including IPE, comparative political economy, international economics, business studies, and business history.